Kekurangan dalam Regulasi Terkait Peralihan Harta Bersama dalam Transaksi Jual Beli Tanah Warisan - Endang Setyowati (Lembaga Pengembangan Kinerja Dosen, 2025)
The land transfer process in Batam City requires a transfer permit from the Batam Supervisory Agency (BP Batam), considering that all land rights in the city are under the Land Management Rights (HPL) regulated by BP Batam based on Presidential Decree Number 41 of 1973. Land that falls into this category requires strict procedures and regulations, including the transfer of rights through a sale and purchase involving authorized parties. This study aims to identify weaknesses in regulations related to the transfer of joint assets, especially inherited land, through current sale and purchase. This study uses a normative juridical approach with a descriptive analysis of applicable laws and regulations, to explore issues related to the transfer of joint assets in the form of inherited land. The main focus of the study is to identify weaknesses in the regulations governing the transfer of rights to inherited land through sale and purchase transactions. The results of the study indicate that the regulations governing the transfer of joint assets in the form of inherited land through sale and purchase have several weaknesses that require attention. These weaknesses consist of three aspects: weaknesses in legal substance, weaknesses in legal structure, and weaknesses in legal culture. In terms of substance, existing regulations do not provide clear and firm provisions regarding the distribution of inherited land rights within the family. Meanwhile, in terms of legal structure, there is still a discrepancy between applicable regulations and current practices. Weaknesses in the legal culture include a lack of understanding and legal awareness in society regarding the transfer of joint property. Therefore, this study emphasizes the need for the state to play a role in protecting the legitimacy of joint property within families, particularly regarding the transfer of inherited land through sale and purchase in Batam City.